Theoretical study of mechanical properties of nanostrands in polymers - Garishin, O.K.; Izumov, R.I.; Lebedev, S.N. (Perm Federal Research Centre Journal, 2017)
Research on computer modeling of the interaction of an atomic force microscopy (AFM) probe with a polymeric nanostrand in the form of a nonlinear elastic cylinder with cantilevered ends and free lateral surface was carried out in the framework of the project. The dimensions of the nanostrand corresponded to the actual values observed in the experiments. Dependencies between the force on the probe, probe indentation depth and nanostrand deflection at different contact points (along the length and in the cross-section) were built. It is shown that the deflection of the strand can be much greater than the depth of the indentation of the AFM probe into the surface. What’s more, the nanostrand in the process of contact can shift not only down, but also sideways. Therefore, standard methods of decoding AFM scan data (which are based on the solution of the problem of contact sphere and flat half-space and the possibility of displacement of the surface as a rigid body is not taken into account) in these cases cannot be used - they give too much error. Ways to solve this problem are given.